Blade work profile during recovery - Kleshnev, V. (BioRow, 2021)
Christian Lindig from Chesterton RC in Cambridge, UK asks: "You have looked at blade work profiles and I notice that they show in general a slight dipping of the hand before the catch. This is generally considered an impediment for a fast catch, but there is also some speculation why we see blade paths that keep the blades so close to the water such that squaring requires dipping the hand: air flow between the feathered blade and the water adds stability. So low blades are not a sign of laziness but taking advantage of this effect. If this is true, I would expect that the "hand dipping" before the catch is more pronounced in small boats (1x, 2x, 2-) than in bigger boats. Bigger boats are more stable and would have less reason to rely on this and maybe pick a different trade-off. Do you see any evidence for this in your data, or is dipping the hands universal across all boat classes?"